Multipotent mesenchymal stromal cells from patients with newly diagnosed type 1 diabetes mellitus exhibit preserved in vitro and in vivo immunomodulatory properties. Issue 1 (December 2016) - Yaochite, Juliana; de Lima, Kalil; Caliari-Oliveira, Carolina; Palma, Patricia; Couri, Carlos; Simões, Belinda; Covas, Dimas; Voltarelli, Júlio; Oliveira, Maria; Donadi, Eduardo; Malmegrim, Kelen
Abstract Background Type 1 diabetes mellitus (T1D) is characterized by autoimmune responses resulting in destruction of insulin-producing pancreatic beta cells. Multipotent mesenchymal stromal cells (MSCs) exhibit immunomodulatory potential, migratory capacity to injured areas and may contribute to tissue regeneration by the secretion of bioactive factors. Therefore, MSCs are considered as a promising approach to treat patients with different autoimmune diseases (AID), including T1D patients. Phenotypical and functional alterations have been reported in MSCs derived from patients with different AID. However, little is known about the properties of MSCs derived from patients with T1D. Since autoimmunity and the diabetic microenvironment may affect the biology of MSCs, it becomes important to investigate whether these cells are suitable for autologous transplantation. Thus, the aim of the present study was to evaluate the in vitro properties and the in vivo therapeutic efficacy of MSCs isolated from bone marrow of newly diagnosed T1D patients (T1D-MSCs) and to compare them with MSCs from healthy individuals (C-MSCs). Methods T1D-MSCs and C-MSCs were isolated and cultured until third passage. Then, morphology, cell diameter, expression of surface markers, differentiation potential, global microarray analyses and immunosuppressive capacity were in vitro analyzed. T1D-MSCs and C-MSCs therapeutic potential were evaluated using a murine experimental model of streptozotocin (STZ)-induced diabetes. Results T1D-MSCs and C-MSCs presented similar morphology, immunophenotype, differentiation potential, gene expression of immunomodulatory molecules and in vitro immunosuppressive capacity. When administered into diabetic mice, both T1D-MSCs and C-MSCs were able to reverse hyperglycemia, improve beta cell function and modulate pancreatic cytokine levels. Conclusions Thus, bone marrow MSCs isolated from T1D patients recently after diagnosis are not phenotypically or functionally impaired by harmful inflammatory and metabolic diabetic conditions. Our results provide support for the use of autologous MSCs for treatment of newly diagnosed T1D patients.